Human pluripotent stem cell (hPSC)-derived microglia for the study of brain disorders. A comprehensive review of existing protocols - Fionicca Teo; Catherine Yen Li Kok; Mao-Jia Tan; H. Shawn Je (IBRO Neuroscience Reports, 2024)
Microglia, resident immune cells of the brain that originate from the yolk sac, play a critical role in maintaining brain homeostasis by monitoring and phagocytosing pathogens and cellular debris in the central nervous system (CNS). While they share characteristics with myeloid cells, they are distinct from macrophages. In response to injury, microglia release pro-inflammatory factors and contribute to brain homeostasis through activities such as synapse pruning and neurogenesis. To better understand their role in neurological disorders, the generation of in vitro models of human microglia has become essential. These models, derived from patient-specific induced pluripotent stem cells (iPSCs), provide a controlled environment to study the molecular and cellular mechanisms underlying microglia-mediated neuroinflammation and neurodegeneration. The incorporation or generation of microglia into three-dimensional (3D) organoid cultures provides a more physiologically relevant environment that offers further opportunities to study microglial dynamics and disease modeling. This review describes several protocols that have been recently developed for the generation of human-induced microglia. Importantly, it highlights the promise of these in vitro models in advancing our understanding of brain disorders and facilitating personalized drug screening.